Answer:
56 + 6(n - 1)
Explanation:
To know which of the equation represent the nth term, we simply test each equation to see the one that will satisfy the table given above.
This can be obtained as follow:
For 56 + 6(n - 1)
1. n = 2
56 + 6(n - 1) = 56 + 6(2 - 1)
= 56 + 6(1)
= 56 + 6
= 62
2. n = 5
56 + 6(n - 1) = 56 + 6(5 - 1)
= 56 + 6(4)
= 56 + 24
= 80
For 56 + 12(n - 1)
1. n = 2
56 + 12(n - 1) = 56 + 12(2 - 1)
= 56 + 12(1)
= 56 + 12
= 68
2. n = 5
56 + 12(n - 1) = 56 + 12(5 - 1)
= 56 + 12(4)
= 56 + 48
= 56 + 24
= 104
For 62 + 6(n - 1)
1. n = 2
62 + 6(n - 1) = 62 + 6(2 - 1)
= 62 + 6(1)
= 62 + 6
= 68
2. n = 5
62 + 6(n - 1) = 62 + 6(5 - 1)
= 62 + 6(4)
= 62 + 24
= 86
For 62 + 12(n - 1)
1. n = 2
62 + 12(n - 1) = 62 + 12(2 - 1)
= 62 + 12(1)
= 62 + 12
= 74
2. n = 5
62 + 12(n - 1) = 62 + 12(5 - 1)
= 62 + 12(4)
= 62 + 48
= 110
From the illustrations made above,
Only equation 56 + 6(n - 1) satisfied the table.
Therefore, the expression 56 + 6(n - 1) can be used to obtain the nth term.